Time trends in stomach cancer mortality across the BRICS: an age-period-cohort analysis for the GBD 2021 - Liu, Dan; Liu, Hao; Wu, Yuhang; Wang, Weihong (Frontiers in Public Health, 2025)
ObjectivesStomach cancer is one of the leading causes of cancer death, and its epidemiologic characteristics are regionally heterogeneous worldwide. The BRICS nations (Brazil, Russian Federation, India, China, and South Africa) have markedly increasing influences on the international stage. We aim to investigate time trends in stomach cancer mortality among the BRICS countries from 1982 to 2021.MethodsData for this study were obtained from the Global Burden of Disease (GBD) 2021 public dataset to investigate the deaths, all-age mortality rate, and age-standardized mortality rate (ASMR) of stomach cancer. The age-period-cohort (APC) model was employed to estimate net drift, local drift, age-specific curves, and period (cohort) relative risks, and the Bayesian generalized linear model was employed to evaluate the relationship between food intake and mortality rate.ResultsIn 2021, there were approximately 572,000 stomach cancer deaths across the BRICS, accounting for 59.9% of global death. Russian Federation exhibited the most significant reduction in ASMR of stomach cancer among the BRICS. In contrast, China continued to report the highest number of stomach cancer deaths. The risk of mortality associated with stomach cancer exhibited a marked increase with advancing age, both within these countries and at the global level. PUFA, sodium, calcium and trans fat may have an impact on the mortality rate of stomach cancer. Favorable trends in period and birth cohort effects were observed in these five nations over the past decades.ConclusionBRICS countries have made varying progress in reducing stomach cancer mortality. Given the diverse environments, it is recommended to progressively develop customized stomach cancer prevention strategies, utilizing available resources. Healthcare services should be extended to all age groups, with a particular emphasis on vulnerable populations.